Nanoparticles Isolated From Porcine Bone Soup Ameliorated Dextran Sulfate Sodium-Induced Colitis and Regulated Gut Microbiota in Mice - Wang, Huiqin; Huang, Jin; Ding, Yanan; Zhou, Jianwu; Gao, Guanzhen; Han, Huan; Zhou, Jingru; Ke, Lijing; Rao, Pingfan; Chen, Tianbao; Zhang, Longxin (Frontiers in Nutrition, 2022)
Daily foods contain a great number of self-assembled nanoparticles which were incidentally produced during food processing. These food incidental nanoparticles can directly access the human gastrointestinal tract in high frequency and large quantities. Limited reports were focused on whether and how these food incidental nanoparticles affected the gastrointestinal tissues and gut microbiota. In the present study, bone soup and its nanoparticles both significantly ameliorated colitis symptoms in DSS-induced mice and inhibited the release of pro-inflammatory cytokines. They also restored intestinal microbiota dysbiosis by improving the diversity and richness of intestinal microbiota and regulating community composition including a remarkable increase in Muribaculaceae, Alistipes, and Alloprevotella, and a decrease in Helicobacter. Moreover, the correlation analysis showed that pro-inflammatory cytokines were negatively correlated with Muribaculaceae, Alloprevotella, and Alistipes, but positively correlated with Helicobacter. These findings suggest that the food incidental nanoparticles can influence human health through regulating the inflammation of the gastrointestinal tissues and the gut microbiota.